2006
DOI: 10.1093/jxb/erl180
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins inhibit epiphyllous plantlet development on leaves of Bryophyllum (Kalanchoe) marnierianum

Abstract: When leaves of Bryophyllum marnierianum are detached from the plant, plantlets develop from primordia located at their margins. Leaves excised with a piece of stem attached do not produce plantlets. Severing the major leaf veins overcomes the inhibitory effect of the attached stem, indicating that the control agent is transmitted through the vascular system. A possible mechanism is that an inhibitory substance, possibly a known plant hormone, transported from the stem to the leaf, suppresses plantlet developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…(Catarino, 1965) reported that cytokinin activated bud development in K. pinnata (Bryophyllum calcynum). In contrast, cytokinin was found to play a central role in the suppression of plantlet primordium development in the leaf (Kulka, 2006). Our study complements the results of Kulka in that the expression of the SAHH gene (contig 32) under drought stress (with plantlets) was more than threefold greater than in the control (no plantlets).…”
Section: Discussionsupporting
confidence: 82%
“…(Catarino, 1965) reported that cytokinin activated bud development in K. pinnata (Bryophyllum calcynum). In contrast, cytokinin was found to play a central role in the suppression of plantlet primordium development in the leaf (Kulka, 2006). Our study complements the results of Kulka in that the expression of the SAHH gene (contig 32) under drought stress (with plantlets) was more than threefold greater than in the control (no plantlets).…”
Section: Discussionsupporting
confidence: 82%
“…The formation of miniature plants on the leaves of Bryophyllum species has intrigued biologists since Goethe (1820) . In some species such as B. daigremontianum , plantlets develop spontaneously on leaves attached to the plant ( Henson and Wareing, 1977 ) whereas in other species such as B. calycinum ( Goethe, 1820 ), B. fedschenkoi , and B. marnierianum ( Kulka, 2006 ), plantlets develop only when the leaves are detached from the plant. The latter type of species is convenient for studying the regulation of plantlet formation as the development can be induced at any time by leaf excision.…”
Section: Introductionmentioning
confidence: 99%
“…Although some papers, when taken together, hinted at an answer to this question ( Loeb, 1915 ; Henson and Wareing, 1977 ; Yazgan and Vardar, 1977 ), no definitive solution was reached. In this laboratory, a related species, B. marnierianum , was used to study the question of plantlet primordium dormancy further ( Kulka, 2006 ). The experiments indicated that cytokinins originating in the plant stem maintain plantlet dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Bryophyllum pinnatum is an incessant medicinal plant that grows in the wild and used as a traditional medicinal as well as ornamental plant in tropical America and Africa, India, Australia, and China. The genus belongs to the family of Crassulaceae and is cultivated as ornamental house plant on rocks or in the garden (Kulka, 2006). The present herb under study is routinely called an air plant, Canterbury bell, cathedral bell, life plant and resurrection plant.…”
Section: Introductionmentioning
confidence: 99%